KINERJA KANTOR BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN CABANG MANADO - PURWANTI, LIS; Rumapea, Patar; Tampongangoy, Deysi (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: In practice, the performance of the resulting Government seems to have not yet showed better conditions change significantly. Some government officials still shows low level of accountability, responsiveness and efficiency in the conduct of the service. Effected by the importance of the role of institutional performance on one side and the number of issues that bind them on the other hand, issues concerning the performance of the institutions as well as public service apparatus became one of the important issues in the reform of public administration in different countries, including for the context of Indonesia at the present time. The performance of the public service are often interchangeable with government performance measurement, it is not too surprising since basically the public service became the responsibility of the Government and related agencies that provide services to the community. BPJS health is a legal entity formed for national health assurance program organize (JKN) and is responsible to the President and has the task to organize national health guarantee.Based on some of the opinions or theories of performance then the author refers to the performance of theory Kumorotomo which States that the performance can be formulated through indicators-charge indicators will namely, efficiency, effectiveness, fairness and responsiveness. The reason this performance theory used is that problems are found, the situation can be solved or sought solution by using the performance theory. This research is a descriptive methode using qualitative approach by digitally describe data obtained from research results about Performance Office BPJS Health Branch of Manado. In qualitative research, data collection is done by observation, in-depth interviews and documentation. The overall conclusion of all indicators that there is, the performance of the Office organizer of social security (BPJS) to Manado Branch Health currently is already quite good, in terms of efficiency because of the service in accordance with the procedure. For effectiveness, it's been pretty good, but should be optimized again about the socialization of social security program so that people understand the concept of JKN, system funding, aware of the benefits to the community as well as the procedures for his service to the service of their health. And then for Justice is already good enough. And responsiveness, the overall service provided to the community already is good enough just yet to a maximum until the required leadership role in directing and supervising the performance of the employee in order that the overall performance is better.Keywords : BPJS Health office performance